Ecotourism Development Strategy of Mangrove Forest in Kurau Timur Village, Koba District, Bangka Tengah Regency - Henri Henri; Gea Ratri Ningsih; Novyandra Ilham Bahtera (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2023)
East Timur Village has pristine mangrove areas. It has much potential that can be developed, one of which is mangrove ecotourism which is directly managed by the people of East Kurau Village. Mangrove ecotourism still need to optimize its potential tourism destination object. The research aims to formulate a development strategy for Mangrove Ecotourism in East Kurau Village, Koba District, Central Bangka Regency. The research uses a qualitative approach with IFAS (Internal Factors Analysis Strategy) and EFAS (External Factors Analysis Strategy). The data is collected through in-depth interviews with related stakeholders, questionnaires distributed to tourists, and field observations. Moreover, the indicators used to measure the data include accessibility, infrastructure, and other supporting aspects. The ecotourism strategy is answered using the SWOT analysis method. The results from matrix calculations of IFAS and EFAS show that the value of the X-axis was 0.93 and of the Y-axis was 0.88. This indicates that the strategic position was at the quadrant I, with the strategic formulation of S-O (aggressive strategy). Some strategies have been formulated, including: Supporting mangrove conservation and creative economic business management; Establishing cooperation in providing supporting infrastructure; Optimizing cooperation in providing education on the benefits of mangroves; and Increasing the government’s commitment to mangrove development.